Distribution of UV light-induced damage in a defined sequence of human DNA: detection of alkaline-sensitive lesions at pyrimidine nucleoside-cytidine sequences. - Lippke, J A (1981)
The distribution of UV light-induced damage to the highly reiterated alpha sequence of human DNA was investigated. The results show that the distribution of UV light-induced cyclobutane dimers within a defined sequence is similar whether the DNA is exposed to UV light as part of the chromosome of intact cells or as naked DNA. However, the cellular environment shields the nuclear DNA, resulting in about 50% decrease in apparent dose. A new type of UV photodamage was detected. Treatment of UV light-irradiated DNA with hot alkali results in strand breaks at positions of cytidine located 3' to pyrimidine nucleosides. The chemical nature and biological significance of the pyrimidine nucleoside-cytidine lesion is discussed.